TUHFAH AL-MAUDUD BI AHKAM AL-MAULUD WRITTEN BY IBNU QAYYIM AL-JAUZIYYAH (PRENATAL EDUCATION STUDY) - Sadiyah, Khalimatus; Mahalli, Mahalli (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Child is a precious gift of God. Because child is an asset of parents to continue the ideals and desires in obtaining happiness, both in the world and in the hereafter. Therefore, the child must be educated and well prepared in order to become a moral and qulified child. Education for child is not only done when they have been born alone, but it should be done when the child is still in the womb (prenatal). Child education in the womb should be really considered by the parents, because it is the beginning of the role of education for a human being, as the foundation of education in the next stage. But the problem that often arises is prenatal education is still often regarded as a form of hereditary tradition. Keeping the child in the womb is just performing a duty of parents to have a healthy child, perfectly born, not disabled and not a miscarriage. So, the efforts undertaken by parents to keep the child in the womb is still limited to physical thing. This paper aims to know the concept of prenatal education according to Ibn Qayyim al-Jauziyyah in the Book of Tuhfah al-Maudud bi Ahkam alMaulud and its relevance to the development of education today.